FCE Practice Exam Papers 1. For the Cambridge English First FCE/FCE(fs) Examination: teacher's book - Evans V. Virginia (Newbury, Express Publishing, 2019)
The book is aimed at learners of the English language at CEF level B2 preparing for the Cambridge English First FCE/FCE(fs) Examination or any other examinations at the same level of difficulty. Key Features: 10 complete practice tests written in the same format as the examination itself; Further practice on Word Distractors, Open Cloze Sentences, Key Word. Transformations and Word Formation. Glossary of all words tested in Paper 1 - Part 1 as well as in the Further Practice section.